2017
DOI: 10.15252/embr.201744045
|View full text |Cite
|
Sign up to set email alerts
|

Local translation in neuronal compartments: how local is local?

Abstract: Efficient neuronal function depends on the continued modulation of the local neuronal proteome. Local protein synthesis plays a central role in tuning the neuronal proteome at specific neuronal regions. Various aspects of translation such as the localization of translational machinery, spatial spread of the newly translated proteins, and their site of action are carried out in specialized neuronal subcompartments to result in a localized functional outcome. In this review, we focus on the various aspects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
151
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(155 citation statements)
references
References 217 publications
(344 reference statements)
2
151
2
Order By: Relevance
“…Growing evidence has suggested that local translation near the stimulated spines occurs, and influences cytoskeletal remodeling during spine morphogenesis (Jung et al, 2014; Rangaraju et al, 2017). We next discuss molecular networks controlling local translation and its implications for spine structural plasticity.…”
Section: Protein Synthesis-dependent Remodeling Of the Spinementioning
confidence: 99%
“…Growing evidence has suggested that local translation near the stimulated spines occurs, and influences cytoskeletal remodeling during spine morphogenesis (Jung et al, 2014; Rangaraju et al, 2017). We next discuss molecular networks controlling local translation and its implications for spine structural plasticity.…”
Section: Protein Synthesis-dependent Remodeling Of the Spinementioning
confidence: 99%
“…In neurons, mRNAs can be trafficked to distant sites in axons and dendrites for local translation and processing [52][53][54][55][56][57]. A range of neuronal transmembrane proteins, including AMPARs, NMDARs and GABA B Rs, can be translated using both somatic and dendritically localised ribosome patterned rough ER.…”
Section: Local Dendritic Translation and Secretory Pathway Traffickingmentioning
confidence: 99%
“…These locally generated proteins contribute to growth and function of axons as well as retrograde signaling for injury responses and survival in the peripheral nervous system (PNS) (2,3). The transport of mRNAs into axons and their translation within axons can be regulated by extracellular stimuli (4).…”
Section: Introductionmentioning
confidence: 99%